Incidence of invasive non-typhoidal Salmonella in Blantyre, Malawi between January 2011-December 2019 [version 1; peer review: 2 approved] - Heather Galloway; Nicholas A. Feasey; Brigitte Denis; Melita Gordon; Clemens Masesa; Catherine N. Wilson; Angeziwa Chunga; Sithembile Bilima; Niza Silungwe (Wellcome Open Research, 2022)
Background: The Malawi-Liverpool Wellcome Trust Clinical Research Programme (MLW) has undertaken sentinel surveillance of bloodstream infection and meningitis at Queen Elizabeth Central Hospital (QECH), Blantyre, Malawi for 20 years. Previously, three epidemics of Salmonella bloodstream infection have been identified. Here we provide updated surveillance data on invasive non-typhoidal Salmonella disease from 2011 – 2019. Methods: Surveillance data describing trends in invasive non-typhoidal Salmonella disease and associated antimicrobial susceptibility profiles are presented for the period January 2011 – December 2019. Results: Between January 2011-December 2019, 128,588 blood cultures and 40,769 cerebrospinal fluid cultures were processed at MLW. Overall, 1.00% of these were positive for S. Typhimurium, 0.10% for S. Enteritidis, and 0.05% positive for other Salmonella species. Estimated minimum incidence of invasive non-typhoidal Salmonella (iNTS) disease decreased from 21/100,000 per year in 2011 to 7/100,000 per year in 2019. Over this period, 26 confirmed cases of Salmonella meningitis were recorded (88.5% S. Typhimurium). Between 2011-2019 there was a substantial decrease in proportion of S. Typhimurium (78.5% to 27.7%) and S. Enteritidis (31.8% in 2011 to 0%) that were multidrug-resistant. Resistance to fluoroquinolones and third-generation generation cephalosporins (3GC) remained uncommon, however 3GC increased amongst Salmonella spp. and S. Typhimurium in the latter part of the period. Conclusions: The total number of iNTS bloodstream infections decreased between 2011-2019. Although the number multidrug resistance (MDR) S. Typhimurium and S. Enteritidis isolates has fallen, the number of MDR isolates of other Salmonella spp. has increased, including 3GC isolates.